CLINICAL AND BIOCHEMICAL INDICATORS IN WHITE RATS IN THE TREATMENT OF EXPERIMENTAL GENERALIZED PARODONTITIS - Yu.I. Silenko; M.V. Khrebor; Y.M. Silenko; O.A. Pisarenko (Ukrainian Medical Stomatological Academy, 2018)
A number of scientists put forward and confirmed the assumption of the presence in the body of biological regulators, polypeptides, carrying out the transfer of information necessary for the functioning, development and interaction of cell populations. The problem of studying the mechanism of action and clinical application of polypeptides is key in modern medicine. The aim of the research is to examine the clinical parameters and the state of free radical oxidation in blood and periodontal tissues of white rats in the treatment of spontaneous generalized periodontitis with the use of polypeptides. Materials and methods of the research. Experiments were performed on 280 six-month-old of rats Wistar line of both sexes weighing 120-130 g. During the study, the animals were kept under vivarium conditions in individual cells, food and water were not limited. All animals were divided into the following groups: Group I - intact animals (70), Group II - animals with spontaneous periodontitis (70), Group III - animals with spontaneous periodontitis, treated with thymalin polypeptide preparation in a dose of 0.1 mg / kg i / m daily, for 10 days (70), Group ІV - animals with spontaneous paradontitis, treated with parodontylin polypeptide preparation at a dose of 1 mg / kg i / m, daily for 10 days (70). Blood for research in rats was taken against the background of hexenalum anesthesia with a syringe from the heart into a plastic syringe. Subsequently, it was mixed with sodium citrate (3.8% solution) in a ratio of 9:1 and centrifuged at 1500 rpm for 10 min. Periodontal tissues and jaws of animals were taken and examined immediately after euthanasia. For the study, the collection of periodontal tissues (gums with periosteum) was performed in the area of the upper and lower molars, since periodontitis often affects these tissues. Indicators of free radical oxidation were determined in blood and periodontal tissues. Resorption of bone tissue of the alveolar process was evaluated. Results and discussion. In the treatment of experimental spontaneous periodontitis using thymalin on the 7th day of observations, regression of symptoms of the disease in animals was observed. Hyperemia and edema, bleeding gums remitted. Whereas under the influence of thymalin there is a regression of dental symptoms by 3.8 times, under the influence of parodontylin - by 7.2 times. The condition of periodontal tissues in animals improved more significantly on the 20th day of observation, the scale assessment of dental status indicates that in animals, treated with thymalin, it is 1.1, and by parodontylin - 0.3 points per animal. In studying the processes of lipid peroxidation in periodontal tissues, their significant reduction in rats with spontaneous periodontitis after administering parodontylin has been established. We also observed an increase in the activity of antioxidant enzymes. Hence, the activity of SOD was twice as high, catalase - by 1.95 times. Reactions of lipid peroxidation had the same dynamics in the blood of animals after administering periodontal polypeptides and thymalin, as in periodontal tissues. We observed a significant decrease in the level of conjugated dienes, the concentration of the latter reaches the value of indices of intact animals. Similar results were obtained with regard to the level of TBA-active products, accumulation of MDA, spontaneous hemolysis of erythrocytes. Attention is drawn to the fact that parodontylin reduced lipid peroxygenation of blood to a greater extent than thymalin. We also observed increased activity of SOD, and, on the other hand, the concentration of ceruloplasmin decreased by 25.4%. Thus, administering periodontal polypeptides during spontaneous periodontitis leads to a decrease in the responses of lipid peroxidation in periodontal tissues and blood. To a greater extent this effect is characteristic of parodontylin in comparison with thymalin.